Multimodality Treatment of Pediatric and Adult Patients With Ewing Sarcoma: A Single-institution Experience. Issue 5 (July 2015) - Diaz-Beveridge, Robert; Lorente, David; Torres, Barbara; Cañete, Adela; Rodrigo, Esteban; Bruixola, Gema; Berlanga, Pablo; Reche, Encarnacion; Montalar, Joaquin; Verdeguer, Amparo; Aparicio, Jorge
Abstract : Introduction: The treatment of Ewing Sarcoma family of tumors is multimodal, both in children and adults. Axial location and metastases are classic prognostic factors. However, the worse prognosis in older patients is more controversial. Methods: Retrospective analysis was performed of pediatric and adult patients treated with the 2001 SEOP protocol: 6 cycles of VIDE chemotherapy (CT). If no progression was observed, local (surgery and/or radiotherapy) and consolidation treatments were performed adjusted to prognosis: 8 cycles of VAC in standard-risk patients or 1 cycle of VAC and high-dose CT and autologous transplant in the case of increased risk. We analyzed induction CT toxicity, type of consolidation treatment, and disease-free (DFS) and overall (OS) survival by the Kaplan-Meier method, with a log-rank analysis of prognostic factors with regard to OS. Results: Thirty-six patients were analyzed (2003 to 2011). Sixty percent were male, with a median age of 16 years (range, 7 to 57 y). The most frequent location was axial (43%), followed by extremities (34%), extraosseous (18%), and ribs (9%). Fifty-four percent of patients had metastases, of which, 58% were pulmonary. The median follow-up period was 36 months (5 to 101 mo). Median DFS was 25 months (16 to 34 mo) and median OS 29 months (19 to 40 mo), with a 3-year OS of 40%. Median OS from progression was 7 months (0.4 to 15 mo). Age <15 years and normal lactate dehydrogenase levels were associated with prolonged OS. Conclusions: Induction CT with the VIDE regimen was feasible in most patients, with a low risk for early progression. Hematological toxicity was substantial but manageable. Adult patients had a worse prognosis. Survival after progression was dismal.